Breastfeeding Self-Efficacy and the Use of Prescription Medication: A Pilot Study - Cynthia Mannion; Deborah Mansell (Obstetrics and Gynecology International)
Objective. To examine the association of self-efficacy, perception of milk production, and lactating women’s use of medication prescribed to increase breast milk in a cohort of 18–40-year-old mothers over six months. Methods. Mothers (n=76) attending community clinics completed the Breastfeeding Self-Efficacy Scale and the Humenick/Hill Lactation Scale, a measure of perceived milk production, three times. Results. Domperidone, a dopamine antagonist, was used by 28% of participants. On average, those using domperidone had lower self-efficacy scores than those not using it (P<0.05) and were more likely to have used formula (Pearson chi-square test statistic =6.87, df=1, P<0.05). Breastfeeding self efficacy and perception of milk production were positively correlated. Conclusion. Breastfeeding assessment conducted prior to prescription of galactogogues is recommended for mothers and healthy term babies. Following Baby-Friendly hospital protocols and increasing self-efficacy for lactating women may be most effective in sustaining breastfeeding. Risks and benefits of various galactogogues are discussed.